The Urgency of Legal Aid in Online Dispute Resolution in the Modernization Era - Teddy Prima Anggriawan; Farizza Taralita Arrachma Fachrezzi; Uzlifatus Dea Arianty; Azizah Kaltsum Mabrukah (Journal of Law, Politic and Humanities, 2024)
Legal aid is one of the protections of constitutional rights for every citizen, which is equally protected under the law. The provision of legal aid in this era of modernization is essential to provide a means of protecting human rights as an implementation of legal protection guarantees. According to the concept of legal aid, which is linked to the aspiration for societal welfare, this is a very important instrument in the implementation of the judicial system, which is crucial for society in Indonesia. Therefore, the urgency of online legal aid established in the modernization era is highly necessary to support public understanding regarding the use of online legal aid to facilitate more practical access to legal assistance. This study uses normative legal research methods with a conceptual and prescriptive approach. Thus, the originality derived from this research is to highlight the urgency of easily accessible online legal aid in the modernization era for the Indonesian public to provide more accessible and flexible legal facilities.